Clinico-etiological profile of neonatal seizures in a tertiary care hospital of Northern India: a prospective cohort study - Rajesh Kumar; Nikki Kumari; Binod Kumar Singh; Md. Athar Ansari (International Journal of Health and Clinical Research, 2021)
Background: Neonates are at higher risk for the development of seizures due to various reasons, however diagnosis of neonatal seizures is difficult to establish because of varied aetiologies involved. Seizures are one of the most common risk factor for neonatal mortality and subsequent long term neurological sequelae. The incidence of neonatal seizure (NS) varies from 1.8-3.5/1000 live birth; whereas in NICU it could be as high as 5/1000 live births. Objectives: The present study was undertaken to evaluate the incidence, etiological factor, biochemical abnormalities, days of onset and clinical types in cases having neonatal seizures.Methods: This was a hospital based descriptive type of observational study done in a Neonatal Intensive Care Unit (NICU) of Department of Pediatrics, Nalanda Medical College & Hospital, Patna, Bihar, India. The study was conducted over a period of 1 year from 1st April 2019 to 31st March 2020 March. 214 neonates fulfilling the inclusion criteria of being < 28 days of life and either presenting with history of seizures or developing seizure during their course of treatment in NICU were included in the study, after consent from parents. They were evaluated with necessary investigations, ultrasound head and CT scan for incidence, etiological factor, clinical types and biochemical abnormalities found in neonatal seizure. Results: Out of 1488 NICU admissions during study period, seizures occurred in 214 neonates. Incidence of NS was 14.38% of total NICU admission. Neonatal seizure occurred more commonly among male (65.4%) than female admissions. 88.3% of NS occurred in babies delivered through spontaneous vaginal delivery. 97.7% neonates with seizure were hospital delivered. Most (68.7%) of these cases had birth weight > 2.5 kg. 90.2% of these case were term babies and only 7.9% were pre-term deliveries. 80.8% were appropriate for gestation age (AGA). 54.7% babies developed seizure within 24 hours of life and total 72% developed seizure within 72 hours of life. Subtle seizure was most common (45.3%) seizure type followed by focal clonic (25.7%), multifocal clonic (11.7%), tonic (7.5%) and myoclonic (2.8%). Birth asphyxia was most common cause seen in 58.4% cases followed by septicaemia/meningitis in 20.6% cases. 42% had biochemical abnormalities but only 9.3% cases had pure metabolic seizure. Hyponatremia was the most common (60.8%) biochemical abnormalities; however hypoglycemia was most common cause for pure metabolic seizure constituting 70% of all pure metabolic seizures. Mortality rate in our study was 15.4% (33 cases, 21 male and 12 female). Most common aetiology leading to death was HIE (58%), followed by infection (24%). Conclusion: Out of total 214 cases, most neonates were normal birth weight, AGA and born through spontaneous vaginal delivery. Majority of neonates had onset of seizure <3 days (<72 hours). Subtle seizure was the most common seizure type and birth asphyxia the most common cause. Health care workers and parents need to be made aware of subtle seizures and the importance of timely and appropriate treatment to decrease any further complications.